The Class Number of Derived Subgroups and the Structure of Camina Groups (Communications in Mathematical Research, 2021)
A finite group $G$ is called a Camina group if $G$ has a proper normalsubgroup $N$ such that $gN$ is precisely a conjugacy class of $G$ for any $g ∈ G − N$. Inthis paper, the structure of a Camina group $G$ is determined when $N$ is a union of2, 3 or 4 conjugacy classes of $G$.